ANALISIS JUMLAH PENDUDUK DAN KEBUTUHAN AIR BERSIH KOTA PURUK CAHU KABUPATEN MURUNG RAYA - Apriadi, Zainul; Jaya, Allan Restu; Nindito, Dwi Anung (Fakultas Teknik, Universitas Wiraraja, 2024)
Puruk Cahu City is the capital of Murung Raya Regency which is geographically located in the position of 0˚51˝ South Latitude - 0˚47˝ North Latitude and 113˚12˝-115˚08˝ East Longitude with an area of 191 km2 and has a population of 20542 people in 2021. As the population increases, the need for clean water will also increase. Therefore, it is necessary to analyze the population and demand for clean water, especially for the next 10 years, namely in 2032 which can be used as a basic reference for calculating the dimensions of clean water treatment plants. To obtain a water demand debit, it is necessary to project the population as well as analyze the water demand for the domestic and non-domestic sectors. In this study, the projection of the population using the least square method in 2032 is 24297 people with a total water demand from both the domestic and non-domestic sectors, namely 42.131 ltr/sec, the maximum daily requirement is 50.588 ltr/sec, and the water demand in the peak hour is 84.263 ltr/sec. This data can be used as a reference for calculating the dimensions of IPA units.